Gaya Komunikasi The Equalitarian Style dalam Pembentukan Karakter Peserta Didik - Bukit, Servista; Tarigan, Ekayanti; Yuni Noviati (Universitas Adiwangsa Jambi, 2023)
The teacher as a facilitator in learning must master communication styles in guiding and teaching students. One of the communication styles that can be mastered by the teacher is the equalitarian style. Through this style of communication the teacher is expected to be able to shape the character of students in the learning process. Communication style is needed by the teacher to communicate with students as an effort to form the character of the students themselves. The formulation of the problem in this research is why the equalitarian style of communication is important to be mastered by teachers in the learning process in order to shape the character of students. The focus of this research is to find out the reasons for the importance of mastering the teacher's communication style with the equalitarian style in building the character of students in the learning process in elementary schools. The theory used in this research is The Equalitarian Style theory of communication style. The type of research used is descriptive qualitative with a literature review approach. The results of this research study are expected to be a stimulus for elementary school teachers in creating effective communication with students through the equalitarian style of communication.